2017
DOI: 10.5384/sjovs.vol10i1p7-17
|View full text |Cite
|
Sign up to set email alerts
|

Looking to the future of visual assessment using driving simulation

Abstract: Visual function is considered uniquely important for driving because it provides multiple critical sources of information that when combined ensures successful steering. There are, however, additional cognitive functions that are essential for the driver to be able to dynamically respond to the world and make predictions about the scene, as well as the behaviour of other road users. Given the complexity of driving through a busy urban environment it should be no surprise that simple tests of visual acuity seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…In contrast to static VF tests, driving simulators can place the same demands on perceptual-motor processes and cognitive functions as real-life driving. (Medeiros et al 2012;Wilkie and Mole 2017) Driving simulators are able to accurately reproduce static visual field tests in a contextual, standardized, safe and reliable setting. (Gangeddula et al 2017;Wilkie and Mole 2017) Few studies have demonstrated the validity of simulator-based driving skills against performance on the road in glaucoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to static VF tests, driving simulators can place the same demands on perceptual-motor processes and cognitive functions as real-life driving. (Medeiros et al 2012;Wilkie and Mole 2017) Driving simulators are able to accurately reproduce static visual field tests in a contextual, standardized, safe and reliable setting. (Gangeddula et al 2017;Wilkie and Mole 2017) Few studies have demonstrated the validity of simulator-based driving skills against performance on the road in glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…(Medeiros et al 2012;Wilkie and Mole 2017) Driving simulators are able to accurately reproduce static visual field tests in a contextual, standardized, safe and reliable setting. (Gangeddula et al 2017;Wilkie and Mole 2017) Few studies have demonstrated the validity of simulator-based driving skills against performance on the road in glaucoma. (Tatham et al 2015) The aims of this pilot study were (1) to compare performance on the newly developed performance-based VF test between drivers with glaucoma and controls, and (2) to investigate the psychometric properties (construct validity, concurrent validity, and test-retest reliability) of the new test.…”
Section: Introductionmentioning
confidence: 99%